2020
DOI: 10.1002/er.5644
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/ β‐ MnO 2 composites—synthesis and its electroanalytical properties study in the Mg storage battery

Abstract: Graphene/β-MnO 2 composites were synthesized via ultrasonication method, followed by calcination at 400 C for 4 hours. The structural properties of synthesized graphene and graphene/β-MnO 2 composites were systematically studied using different instruments, such as XRD, FESEM, TEM, EDX, XPS and FT-IR spectroscopy. Furthermore, magnesium storage performance was scientifically studied using various electroanalytical characterizations like galvanostatic charge/discharge, electrochemical impedance spectra and cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
(72 reference statements)
2
7
0
Order By: Relevance
“…Charge transfer is an important aspect of the adsorption system. 19 Figure 3 shows the schematic diagram of charge transfer between Cs atom and GaN monolayer when Cs is absorbed at different adsorption sites. The figure of charge density difference is also given to observe Mulliken charge distribution.…”
Section: Cs Absorption Of Gan Monolayermentioning
confidence: 99%
See 2 more Smart Citations
“…Charge transfer is an important aspect of the adsorption system. 19 Figure 3 shows the schematic diagram of charge transfer between Cs atom and GaN monolayer when Cs is absorbed at different adsorption sites. The figure of charge density difference is also given to observe Mulliken charge distribution.…”
Section: Cs Absorption Of Gan Monolayermentioning
confidence: 99%
“…PETE device is based on thermionic emission of photoexcited electrons from a semiconductor cathode at high temperature 10 . With the maturity and perfection of nanomaterials and nanotechnology, two‐dimensional (2D) semiconductor materials, represented by graphene, 11‐13 MoS 2 , 14,15 hBN, 16 and so on, gain much attention due to their novel properties and potential applications 17‐19 . These studies show that the physical properties of the atomic‐scale thickness limitation can give 2D semiconductors fascinating electric, mechanic, and thermal properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S9 † ). 30 Therefore, the MnO 2 catalyst would facilitate the generation of ˙OH for efficient degradation.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] It is also observed that non-graphitic pure MWCNTs with EMIM-Cl (1-ethyl-3-methyl imidazolium chloride) ionic liquid electrolyte showed an electrochemical performance with a specific capacity of 64 to 58 mA h g À1 at 99% coulombic efficiency. 35 Recently, we developed a graphene/b-MnO 2 composite system for magnesium batteries, which further inspired us to explore it for AIBs. 36 Manganese dioxide (MnO 2 ) is the foremost cathode material in battery technology because of various benefits, like being abundantly available in the earth's crust, low cost, environmental friendliness, and low toxicity.…”
Section: Introductionmentioning
confidence: 99%